1961
DOI: 10.1172/jci104376
|View full text |Cite
|
Sign up to set email alerts
|

Total Nondialyzable Solids (Tnds) in Human Urine. Ix. Immunochemical Studies of the R-1 “Uromucoid” Fraction*

Abstract: A method has been described for separation of the nondialyzable solids of normal urine into three major fractions (1). The R-1 fraction is composed of the portion which is not filtrable through collodion membranes of average pore diameter 20 mtn, and which is insoluble in veronal buffer of pH 8.6 and ionic strength 0.1. A mean excretion rate of 90 mg per 24 hours (range, 51 to 168 mg per 24 hours) has been established for both male and female adults. Attempts to separate the R-1 into subfractions by electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The fluorescent materials were observed also in tubular lumina and the cell membranes were remained completely unstained. DISCUSSION Boyce et al (1) have demonstrated that the uromucoid antigen was contained in the kidney with a titre decreasing in the order of the cortex, medulla and pelvis. They found it also in the skin, subcutaneous fat and striated muscle, but not in the erythrocyte membrane, saliva, bone matrix and seminal plasma.…”
Section: Resultsmentioning
confidence: 88%
“…The fluorescent materials were observed also in tubular lumina and the cell membranes were remained completely unstained. DISCUSSION Boyce et al (1) have demonstrated that the uromucoid antigen was contained in the kidney with a titre decreasing in the order of the cortex, medulla and pelvis. They found it also in the skin, subcutaneous fat and striated muscle, but not in the erythrocyte membrane, saliva, bone matrix and seminal plasma.…”
Section: Resultsmentioning
confidence: 88%
“…These substances were unginally known as protective colloids but the term is probably not justified as our knowledge of them is incomplete. There are a number of methods of isolation that produce different fractions, some of which have been shown immunologically to be a mixture of mucoproteins (Boyce, King and fielden, 1961). There appear to be at least three types of urinary mucoprotein.…”
Section: Proportion Of Matrix In Various Types Of Calculimentioning
confidence: 99%
“…The rabbit matrix immune serum was prepared by foot-pad injections of suspensions of lyophilized matrix or other antigen in complete Freund's adjuvant (10). Sera from adult rabbits, which had been injected with the same antigen, were pooled.…”
Section: Total Nondialyzable Solids (Tnds)mentioning
confidence: 99%
“…Previously described methods (10), utilizing the Ouchterlony agar gel plates, were followed. The plates with 6 peripheral circular wells of 0.3 ml capacity and 10 mm distance from the center well were suitable for this study, in which comparison of precipitin reactions of a large number of unknowns was desirable.…”
Section: Total Nondialyzable Solids (Tnds)mentioning
confidence: 99%
See 1 more Smart Citation